An implementation of the UTD on facetized CAD platform models. - Hussar, Paul E. (IEEE Antennas & propagation magazine.)
The Aircraft inter-Antenna Propagation with Graphics (AAPG) 2000 computer code relies on realistic computer-aided design (CAD) platform geometrical modeling to support uniform geometrical theory of diffraction (UTD) predictions of antenna-to-antenna coupling for aircraft-mounted antennas. The code employs novel ray-tracing techniques that permit the computation of UTD propagation paths over facetized objects of general shape. Moreover, geometrical data, required by UTD formulations for wedge and smooth-surface diffraction and reflection, are computed entirely from path and facetized-object geometries. Since the entire object representation in AAPG 2000 is in terms of facets, division of path-object interactions into wedge and smooth-surface cases must be performed heuristically.